Pengaruh Program Posbindu PTM terhadap Pengendalian Hipertensi pada Kelompok Usia Produktif di Kecamatan Cimanggis, Kota Depok - Ananda Putrabangsa; Azzahra Nabila (Journal of Applied Health Sciences, 2026)
Hypertension is a major non communicable disease with an increasing prevalence among the productive age population, particularly in urban areas. Low rates of early detection and blood pressure control remain key challenges in reducing cardiovascular complications. The Integrated Development Post for Non Communicable Diseases program, known as Posbindu PTM, was developed as a community based promotive and preventive strategy to enhance screening, health education, and monitoring of hypertension risk factors. This study aimed to analyze the effect of the Posbindu PTM program on hypertension control among the productive age group in Cimanggis District, Depok City. This study employed a quantitative analytic observational design with a cross sectional approach. A total of 150 respondents aged 15 to 64 years who had attended Posbindu PTM activities at least once in the past six months were included. Data were collected using a structured questionnaire and standardized blood pressure measurements with a calibrated digital sphygmomanometer. Data analysis was conducted through univariate analysis, bivariate analysis using the Chi square test, and multivariate analysis using logistic regression to control for confounding variables including age, sex, body mass index, family history of hypertension, and smoking behavior. The results showed that 56 percent of respondents had controlled blood pressure. There was a statistically significant association between regular participation in Posbindu PTM and hypertension control with a p value less than 0.05. Logistic regression analysis indicated that respondents who regularly attended Posbindu PTM were 3.45 times more likely to achieve controlled blood pressure compared to those with low participation. Body mass index also had a significant influence on hypertension control status. This study concludes that the Posbindu PTM program has a positive and significant effect on hypertension control among the productive age population in an urban setting. Strengthening program implementation and increasing participation among the productive age group are essential strategies to prevent hypertension related complications and improve overall community health outcomes.